Ultrasonic Noise Sources in a Work Environment - Bożena SMAGOWSKA (Archives of Acoustics, 2013)
The use of ultrasonic energy has created versatile possibilities of their applications in many areas of life, especially in hydro location and underwater telecommunications, industry and medicine. The consequence of a widespread use of high intensity ultrasonics in technology is the increased number of people who are exposed to such ultrasonic noise. Therefore it is important to determine the types of machines and other devices that are responsible for the emission of ultrasonic noise (10–40 kHz of central frequencies of one-third octave bands) as harmful and annoying hazard in the work environment. This paper presents ultrasonic noise sources frequently used in industry and preventive measures reducing the exposure to ultrasonic noise. Two types of ultrasonic noise sources have been distinguished: machines and other devices used to carry out or improve production processes, the so-called technological sources and sources in which ultrasonic noise exists as a non-intentional result of operation of many machines and systems, the so-called non-technological sources of ultrasonic noise. The emission of SPL has been determined for each groups of devices based on own measurement results.